Theatre of anger : radical transnational performance in contemporary Berlin - Landry, Olivia (German and European studies ;, 2021)
"In Theatre of Anger, Olivia Landry offers a provocative new vision of anger as more than just hate and violence. Studying the work of a new generation of transnational theatre practitioners in Berlin, she illuminates how anger can be an affirmative and critical tool in the project of social justice and resistance. To develop her theory of anger, Landry delves into philosophical texts, theatre history, and Black feminist theory from Aristotle, Gotthold Ephraim Lessing, and Bertolt Brecht to Audre Lorde, bell hooks, and Sara Ahmed. Landry focuses not only on the social and political significance of the theatre of anger and the ways in which it rages against racism, antisemitism, Islamophobia, sexism, and homophobia, but also on its aesthetic and theoretical innovation. Through readings of key works, Theatre of Anger asks what it means in our present world to construct political theatre."--